Carbonation of a blended slag-fly ash geopolymer concrete in field conditions after 8 years. (30th October 2016) - Pasupathy, Kirubajiny; Berndt, Marita; Castel, Arnaud; Sanjayan, Jay; Pathmanathan, Rajeev
Highlights: Carbonation of geopolymer concrete exposed to atmospheric environment was investigated. The mix compositions of geopolymer concrete was influenced on the carbonation rate in atmosphere. The presence of carbonation reaction components was identified by TGA and FTIR analysis. MIP analysis test results was providing a good correlation with carbonation depth values. Abstract: In this study, the carbonation resistance of two geopolymer concretes exposed to outdoor field conditions for eight years was investigated. Core specimens were used to determine the in-situ carbonation depth, concrete porosity was assessed and the carbonation reaction products of aged concrete were identified by TGA and FT-IR analysis. Carbonation of the geopolymer concretes was compared to OPC and fly ash concretes exposed to similar conditions. The results indicated that the carbonation rate of geopolymer concrete is highly dependent on the activator components of geopolymer concrete. Type 1 geopolymer concrete, with 75% fly ash/25% GGBFS and additional Na2 SiO3 activator, showed a poor resistance against carbonation compared to OPC concrete. However, the performance of Type 2 geopolymer with 70% fly ash/30% GGBFS and no additional Na2 SiO3 activator, was similar to OPC concrete. In addition, water absorption, sorptivity, total porosity and differential pore size distribution analysis correlated well with the carbonation resistance. Investigation of long term durability performance of geopolymer concrete is critical for the development of standard specifications for commercial application. This study reveals that two geopolymer concretes, with a similar mix design and compressive strength, have different carbonation behaviour. Therefore, a performance based approach is an appropriate strategy to develop standard specifications for geopolymer concrete.